2012
DOI: 10.1007/s00418-012-0911-x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic chemosensory cells in the auditory tube

Abstract: The luminal composition of the auditory tube influences its function. The mechanisms involved in the monitoring are currently not known. For the lower respiratory epithelium, such a sentinel role is carried out by cholinergic brush cells. Here, using two different mouse strains expressing eGFP under the control of the promoter of choline acetyltransferase (ChAT), we show the presence of solitary cholinergic villin-positive brush cells also in the mouse auditory tube epithelium. They express the vesicular acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…This response was completely dependent on an intact chemosensory signal transduction cascade since TRPM5 deficiency abolished the effect. A similar role has been proposed for chemosensory cells of the auditory tube that might limit the access to the tympanic cavity [7]. Our finding that cholinergic chemosensory cells are present in the ciliated duct of airway glands fits to the concept of chemosensory cells serving sentinel function against intruding agents.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This response was completely dependent on an intact chemosensory signal transduction cascade since TRPM5 deficiency abolished the effect. A similar role has been proposed for chemosensory cells of the auditory tube that might limit the access to the tympanic cavity [7]. Our finding that cholinergic chemosensory cells are present in the ciliated duct of airway glands fits to the concept of chemosensory cells serving sentinel function against intruding agents.…”
Section: Discussionsupporting
confidence: 76%
“…urethra, thymus, thyroid gland, heart, auditory tube, airways and lung [1][2][3][4][5][6][7]. In mucosal epithelia, these chemosensory cells express one or more members of the taste receptor family 1 (Tas1R) (sweet and umami) and Tas2R (bitter) that are coupled to various G-proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that intestinal brush cells appear to be intensively innervated at their basal membrane (Morroni et al 2007) suggests an involvement of classical neurotransmitters. In this regard, it is interesting to note that solitary brush cells in the airways and the auditory tube may be cholinergic, expressing the enzyme choline acetyltransferase (Krasteva et al 2011(Krasteva et al , 2012. Recent immunohistochemical studies using specific antibodies revealed that at least some of the gastric brush cells expressed choline acetyltransferase (unpublished results).…”
Section: Tuft Cells/brush Cellsmentioning
confidence: 93%
“…The presence of the T1R3 receptor protein in some brush cells was recently demonstrated by immunohistochemical approaches (Hass et al 2010). Based on some structural features, gastrointestinal brush cells are considered as members of a larger family of solitary chemosensory cells (Sbarbati et al 2010) which are found in a variety of other tubular organs, including the respiratory epithelium of the nasal cavity (Finger et al 2003;Kaske et al 2007), the tracheal mucosa of the airways (Kaske et al 2007;Lin et al 2008) and the epithelium of the auditory tube (Krasteva et al 2012). Some of the solitary chemosensory cells specifically respond to bitter compounds (Finger et al 2003); whether this is also a feature of some intestinal brush cells remains elusive.…”
Section: Tuft Cells/brush Cellsmentioning
confidence: 99%
“…1A) (6)(7)(8). In the trachea, a related cell type, the chemosensory brush cell, releases acetylcholine (ACh) to activate vagal pain fibers (16)(17)(18), suggesting ACh as a candidate neurotransmitter for SCCs. Similarly, SCCs lining the vomeronasal duct of mice express choline acetyltransferase (ChAT), the synthetic enzyme of acetylcholine (19).…”
Section: Resultsmentioning
confidence: 99%